Efeito do ultrassom na resistência de união de cimentos resinosos autoadesivos à dentina - Silva, Diego Fabris Ferreira da (2012)
The aim of this study was to evaluate the influence of ultrasonic application on bond strength of self-adhesives resin cements to dentin. Twenty-four third molars were randomly divided into 4 groups (n=6/group): G1 - Rely X Unicem; G2 Maxcem Elite; G3 RelyX Unicem and ultrasonic application; G4 Maxcem Elite and ultrasonic application. Composite resin blocks were luted to flat dentin with a load of 500 g for 2 min, followed by light polymerization in G1 and G2. In G3 and G4, the ultrasonic device was applied for 20 s on the composite resin block, followed by 500 g load for 1 min and 40 s, and light polymerization. After storage in distilled water at 37ºC for 24 h, six tooth/resin sets were cut parallel to the long axis of the tooth, in the x and y directions, with a section of about 0.8 mm2. Twenty-four specimens were obtained to each group, and submitted to microtensile bond strength (μTBS) test in an universal testing machine at 0,5 mm/min crosshead speed. According to two-way ANOVA, type of cement factor (p=0.000) and type of luting factor (o=0.002) were significant. The interaction was not significant (p=0676). According to student-t test (α=0.05), the μTBS mean with ultrasonic application (13.74 MPa) was statistically higher than without this treatment (10.57 MPa). The μTBS mean of RelyX Unicem (13.95 MPa) was statistically higher than Maxcem Elite (10.36 MPa). The ultrasonic application increased the μTBS of the RelyX Unicem and Maxcem Elite to dentin.